IMPLEMENTATION OF INNOVATIVE MARKETING TECHNOLOGIES AS A DRIVER FOR THE DEVELOPMENT OF THE UKRAINIAN EXPORT SERVICES MARKET - Семенова, Людмила; Хурдей, Вікторія (SWorldJournal, 2025)
The article explores the impact of innovative marketing technologies on the promotion of services in the international market and on strengthening the export potential of Ukraine. The study emphasizes the role of digital platforms, artificial intelligenc